Citotoxidade e mecanismo de ação de complexos Ru(II)/2-mercapto-4(3H)quinazolinona em células de câncer de pele - Silva, Nádija Natalice Paixão da (Universidade Federal de São Carlos, 2023)
Ruthenium biphosphynic complexes combined with mercapto ligands have shown low IC50 values and good selectivity indexes (SI) in different tumor lines studied, which has motivated the development of ruthenium compounds with these ligands. Therefore, in this work, five complexes were synthesized: [RuCl(H2mq)(dppm)2]PF6 (Ru1), [Ru(2mq)(dppe)2]PF6 (Ru2), [Ru(2mq)(dppen)2]PF6 (Ru3), [Ru(2mq)(bipy)2]PF6 (Ru4) e [Ru(2mq)(dppm)2]PF6 (Ru5) (dppe: bis(diphenylphosphine)ethane; dppm: 1.1'- bis (diphenylphosphine)methane; dppen: 1,2'- bis (diphenylphosphine)ethene; bipy: 2,2'-bipridine; H2mq or 2mq: 2-mercapto-4(3H)quinazolinone). The complexes were characterized by 1D and 2D nuclear magnetic resonance techniques, molar conductance, elemental analysis, absorption spectroscopy in the infrared region and ultraviolet-visible (UV-Vis) region, cyclic voltametry, mass spectrometry and single-crystal X-ray diffraction. The interaction of the complexes with DNA was evaluated by viscosity techniques, circular dichroism, competition assay with Hoechst and CT-DNA, and electrophoresis in agarose gel. The complexes showed weak interaction with this biomolecule, possibly by the grooves and electrostatic. The interaction of the complexes with HSA was also evaluated, using the fluorescence spectroscopy technique, which allowed to verify that the interaction of the complexes with this biomolecule is moderate (×104 M-1). The cytotoxic activity of the complexes was evaluated in tumor lines B16-F10 (murine), A-375 (human melanone) and HaCat non-tumoral (human keratinocytes). The complexes were cytotoxic in the studied lines and presented lower IC50 values than those cisplatin (A-375: 6.95  0.03; B16-F10: 148.11  5.96). Because of the higher selectivity index value obtained for the Ru3 complex (SIA-375: 4,61; SI B16-F10: 2,66), it was selected to continue the investigation of the possible mode of action. The Ru3 complex inhibited the formation of colonies in the HaCat and A-375 cell lines, with more pronounced effect in A-375 and modified the morphology of this cell after 24 h at concentrations above the values IC50. In the Wound Healing assay, it was observed that Ru3 inhibited cell migration at concentrations of 0,2 and 0,4 μM.
Cytoxity and mechanism of action of Ru(II)/2-mercapto-4(3H)quinazolinone complexes in skin cancer cells
Keywords: Mercapto; Câncer de pele; Complexos de rutênio; Skin cancer; Ruthenium complexes; CIENCIAS EXATAS E DA TERRA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::CAMPOS DE COORDENACAO; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA